THE EFFECT OF PRICES AND SOCIAL MEDIA ON THE INCOME OF CHILI SEED FARMERS IN JEBUNG KIDUL VILLAGE, TLOGOSARI DISTRICT BONDOWOSO REGENCY - Maidatul Imamah; Widya Anggita Putri; Izzah Dienillah; Ahmad Hendra Rofiullah; Ahmad Muhyidin (International Conference on Humanity Education and Society (ICHES), 2025)
The agricultural sector in Indonesia plays an important role in the economy, contributing around 13% to GDP and providing employment for the majority of the population. However, farmers face challenges such as price fluctuations and limited access to market information, impacting their income. Farm income is heavily influenced by the price of agricultural products, and low prices can result in losses. Advances in digital technology, especially social media, open up opportunities for farmers to access market information and improve competitiveness. This study aims to analyze and determine the effect of price and social media on the income of chili seedling farmers in Jebung Kidul village. This type of research uses descriptive with a quantitative approach, the sample is taken using the Simple Random Sampling method and the data collection method uses a questionnaire. A total of 155 as respondents. Hypothesis analysis was carried out using multiple linear regression techniques. The results showed that (1) price has a significant effect on the income of chili seed farmers in Jebung Kidul village and (2) social media has no significant effect on the income of chili seed farmers in Jebung Kidul village. (3) Price and social media have a significant influence on the income of chili seedling farmers in Jebung Kidul village.